Ecological Messages In The Ramayana Story Of The Wayang Purwa Shadow-Puppet Play - Djoko Sulaksono; Kundharu Sadhhono (Lekesan: Interdisciplinary Journal of Asia Pacific Arts, 2019)
The aim of this research is to describe ecological messages in the Ramayana story of the wayang purwa shadow-puppet play. As a qualitative research, it used descriptive analysis techniques and ecology studies based on data derived from ecological content in the Ramayana story. Results from the analysis show that several ecological forms in the Ramayana story can be described and viewed from the interactions between characters in the story and fellow human beings, water, land, fire, air, plants and animals. These interactions point to a reciprocal relationship between living things and the environment. The results of this study enrich the treasure of knowledge in the field of literature and provide a picture for communities about the relationship between living things and the environment, which should be aligned with guidance within Javanese society. Through this research, communities are invited to respect each other’s existence and living things in their surroundings. This is because everything in the world is believed to have its respective strengths and benefits.